Emotion in organizational change : an interdisciplinary exploration - Talat, Usman (Springer, 2017)
This book constructs a multi-disciplinary interpretation of emotion, specifically applied and discussed within Organizational Change environments. Including a range of perspectives from Philosophy, Evolutionary Sciences, Psychology and Sociology, Emotion in Organizational Change also provides a historical picture of our knowledge of emotion. The author explores how this can contribute towards a novel understanding of a pervasive phenomenon in society and its organizations. Usman Talat is a Lecturer in People Management at the University of Salford, UK. His research interests include Philosophy, Evolutionary psychology, and Organizational change.
Keywords: Organizational change -- Psychological aspects.; Emotions.; elektronické knihy; electronic books